2022
DOI: 10.1007/s40123-022-00483-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vessel Density as Measured by Optical Coherence Tomography Angiography in the Evaluation of Pseudoexfoliative Glaucoma: A Review of the Literature

Abstract: Introduction:To review the existing literature about the optical coherence tomography angiography (OCTA) findings regarding peripapillary and macular vessel density (VD) in patients with pseudoexfoliative glaucoma (PXG). Methods: A comprehensive search of the PubMed database was conducted to include articles up to November 1, 2021, using an appropriate search algorithm. The retrieved articles were assessed for eligibility and filtered manually to exclude duplicates, while articles and book chapters cited in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Recently, Chatziralli et al found that the peripapillary and MVD were lower in eyes with pseudoexfoliative glaucoma (PXG) [37]. This indicates optic nerve hypoperfusion may play a greater role in patients with PXG.…”
Section: Optical Coherence Tomography Angiography Features Of the Cho...mentioning
confidence: 99%
“…Recently, Chatziralli et al found that the peripapillary and MVD were lower in eyes with pseudoexfoliative glaucoma (PXG) [37]. This indicates optic nerve hypoperfusion may play a greater role in patients with PXG.…”
Section: Optical Coherence Tomography Angiography Features Of the Cho...mentioning
confidence: 99%